2017
DOI: 10.1021/acsami.7b08473
|View full text |Cite
|
Sign up to set email alerts
|

Post-polymerization C–H Borylation of Donor–Acceptor Materials Gives Highly Efficient Solid State Near-Infrared Emitters for Near-IR-OLEDs and Effective Biological Imaging

Abstract: Post-polymerization modification of the donor-acceptor polymer, poly(9,9-dioctylfluorene-alt-benzothiadiazole), PF8-BT, by electrophilic C-H borylation is a simple method to introduce controllable quantities of near-infrared (near-IR) emitting chromophore units into the backbone of a conjugated polymer. The highly stable borylated unit possesses a significantly lower LUMO energy than the pristine polymer resulting in a reduction in the band gap of the polymer by up to 0.63 eV and a red shift in emission of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 41 publications
2
46
0
2
Order By: Relevance
“…More recently,He et al described the Suzuki-Miyaura and Stille copolymerization of B À Np henanthrene derivatives that are derived from ring-expansion of 9-borafluorenes with aromatic azides. [181] Theo rganoboron component may be viewed as an analog of cyclopentadithiophene, ac ommon building block in organic electronics,b ut placement of the B-N unit lowers both the HOMO and LUMO energy levels,t hus dramatically enhancing the acceptor character.T he borane functionalization of N-heterocyclic polymers can also be achieved in ap ost-polymerization modification as demonstrated by Ingleson, Tu rner et al [182] They used the Lewis base directed electrophilic borylation of 107 to generate homopolymer 108 and related partially borylated copolymers (Scheme 12 b). [180] Using aC ÀNc helated borane monomer,L iu et al developed tetracoordinate borane polymers as new acceptor materials for OSC applications.T hey demonstrated that the combination of borane-complexed thienylthiazolyl units with organic electron-acceptors results in n-type materials that are highly effective in all-polymer solar cells giving PCEs as high as 5% (106,S cheme 12 a).…”
Section: Other Polymers Containing Conjugated Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently,He et al described the Suzuki-Miyaura and Stille copolymerization of B À Np henanthrene derivatives that are derived from ring-expansion of 9-borafluorenes with aromatic azides. [181] Theo rganoboron component may be viewed as an analog of cyclopentadithiophene, ac ommon building block in organic electronics,b ut placement of the B-N unit lowers both the HOMO and LUMO energy levels,t hus dramatically enhancing the acceptor character.T he borane functionalization of N-heterocyclic polymers can also be achieved in ap ost-polymerization modification as demonstrated by Ingleson, Tu rner et al [182] They used the Lewis base directed electrophilic borylation of 107 to generate homopolymer 108 and related partially borylated copolymers (Scheme 12 b). [180] Using aC ÀNc helated borane monomer,L iu et al developed tetracoordinate borane polymers as new acceptor materials for OSC applications.T hey demonstrated that the combination of borane-complexed thienylthiazolyl units with organic electron-acceptors results in n-type materials that are highly effective in all-polymer solar cells giving PCEs as high as 5% (106,S cheme 12 a).…”
Section: Other Polymers Containing Conjugated Heterocyclesmentioning
confidence: 99%
“…[180] Using aC ÀNc helated borane monomer,L iu et al developed tetracoordinate borane polymers as new acceptor materials for OSC applications.T hey demonstrated that the combination of borane-complexed thienylthiazolyl units with organic electron-acceptors results in n-type materials that are highly effective in all-polymer solar cells giving PCEs as high as 5% (106,S cheme 12 a). [181] Theo rganoboron component may be viewed as an analog of cyclopentadithiophene, ac ommon building block in organic electronics,b ut placement of the B-N unit lowers both the HOMO and LUMO energy levels,t hus dramatically enhancing the acceptor character.T he borane functionalization of N-heterocyclic polymers can also be achieved in ap ost-polymerization modification as demonstrated by Ingleson, Tu rner et al [182] They used the Lewis base directed electrophilic borylation of 107 to generate homopolymer 108 and related partially borylated copolymers (Scheme 12 b). Theb orylation induces large red-shifts in absorption and emission and, hence,t hese polymers strongly emit in the NIR region.…”
Section: Other Polymers Containing Conjugated Heterocyclesmentioning
confidence: 99%
“…Mit einem noch grçßeren konjugierten p-System stellten Pei et al konjugierte Polymere aus einem B-N-substituierten Tetrathienonaphthalin her und demonstrierten eine hohe Effizienz in OFET-Anwendungen (105; Abbildung 28, unten rechts). [182] Sie nutzten die Lewis-Basen-gesteuerte elektrophile Borylierung von 107,umHomopolymer 108 und verwandte teilborylierte Copolymere zu erzeugen (Schema 12 b). [181] Die Organobor-Komponente kann als Analogon von Cyclopentadithiophen, einem gängigen Baustein in der organischen Elektronik, be-trachtet werden, aber die Platzierung der B-N-Einheit senkt sowohl die HOMO-als auch die LUMO-Energiewerte und verbessert damit den Akzeptorcharakter drastisch.…”
Section: Angewandte Chemieunclassified
“…Die Boran-Funktionalisierung von N-heterocyclischen Polymeren kann auch durch eine Modifizierung nach der Polymerisation erreicht werden, wie Ingleson, Tu rner et al zeigten. [182] Sie nutzten die Lewis-Basen-gesteuerte elektrophile Borylierung von 107,umHomopolymer 108 und verwandte teilborylierte Copolymere zu erzeugen (Schema 12 b). Die Borylierung bewirkt eine ausgeprägte Rotverschiebung in Absorption und Emission, und daher emittieren diese Polymere stark im Nahinfrarot(NIR)-Bereich.…”
Section: Angewandte Chemieunclassified
“…BCl 3 ). [8] Post CÀHb orylation the cross-coupling step will occur at ap osition that creates significant steric crowding and thus will lead to twisting in the DÀAm olecule. While directed electrophilic CÀHb orylation has been utilised to incorporate boracyclesi nto DÀAc ompounds to reducet he LUMO energy,i ncluding in TADF emitters (compound C), [7b, 9] the combination of directed electrophilicC ÀHb orylation with sequential Suzuki-Miyaura cross-coupling is much less explored, [10] and to date has not been used to make highly twisted DÀAc ompounds to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%